Analisis Kebutuhan Energi di Universitas Nusa Cendana Tahun 2018-2050 Menggunakan Perangkat Lunak Long-range Energy Alternative Planning system (LEAP) - Yorim A. Masus; Ben V. Tarigan; Jefri S. Bale (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2019)
Energy management in an agency, especially at the University of Nusa Cendana, is still very high dependence on fossil energy. The growth in consumption of electricity and fuel oil continues to increase by an average of 20% per year. Changes in energy consumption are increasing due to changes in power tariffs from 13.2 killovolt amperes (kVa) to 650 killovolt amperes (kVa). In projecting energy demand, the author uses LEAP Software (Long-range Energy Alternative Planning system) version 2017.011.0 from 2018-2050. The purpose of this study was to analyze and determine the treatment of the dependent and independent variables on the magnitude of the results of energy needs at the University of Nusa Cendana. The projection results obtained from the total final energy demand of the Undana sector which is estimated to reach 1,685 kilowatts by 2050 or equivalent to 1.7 megawatts with an average growth of 30%. Meanwhile, for the transportation sector, the final energy demand for fuel (diesel and premium) for vehicle operations is estimated to reach 150.8 thousand barrels by 2050 with an average growth of 38%. The elasticity of energy used shows an increase of 1% after 2018. Energy conservation in the user sector shows potential efficiency of 716.7 kilowatts or equivalent to 0.717 megawatts in 2050, with an average growth of 37% against the Business As Ussual (BAU) scenario.